The protective effects of whortleberry extract against cisplatin-induced ototoxicity in rats - Özdemir,Doğukan (2019)
Abstract Introduction: Cisplatin is one of the main chemotherapeutic agents used for the treatment of many types of cancer. However, ototoxicity, one of the most serious side effects of cisplatin, restricts its usage. Objective: We aimed to investigate the protective effects of whortleberry extract against cisplatin-induced ototoxicity by evaluating hearing and histopathological cochlear damage and by measuring the biochemical parameters affected byoxidative stress. Methods: Forty-eight male rats were included in the study after performing Distortion Product Otoacoustic Emission test to confirm that their hearing levels were normal. The rats were randomly divided into six groups: the control group, the sham group, and, which received only whortleberry extract, only cisplatin, cisplatin + 100 mg whortleberry extract, cisplatin + 200 mg whortleberry extract, respectively. Audiologic investigation was performed by performing the Distortion Product Otoacoustic Emission test at the beginning and at the eighth day of the study. Cardiac blood samples were collected for biochemical analysis, and the rats were sacrificed to obtain cochlear histopathological specimens on the eighth day. Results: The results revealed that whortleberry protects hearing against cisplatin-induced ototoxicity independent of the dose. However, high doses of whortleberry extract are needed to prevent histopathological degeneration and oxidative stress. Conclusion: The results obtained in this study show that whortleberry extract has a protective effect against cisplatin-induced ototoxicity.